Conversation analysis and second language pedagogy : a guide for ESL/EFL teachers - Wong, Jean; Waring, Hansun Zhang (New York : Routledge, Taylor & Francis Group, 2021)
"Now in its second edition, this volume offers a strong synthesis of classic and current work in conversation analysis (CA), usefully encapsulated in a model of interactional practices that comprise interactional competence. Through this synthesis, Wong and Waring demonstrate how CA findings can increase language teachers' awareness of the spoken language and suggest ways of applying that knowledge to teaching second language interaction skills. The Second Edition features: Substantial updates that include new findings on interactional practices Reconceptualized, reorganized, and revised content for greater accuracy, clarity, and readability Expanded key concepts glossary at the end of each chapter New tasks with more transcripts of actual talk New authors' stories The book is geared towards current and prospective second or foreign language teachers, material developers, and other language professionals, and assumes neither background knowledge of conversation analysis nor its connection to second language teaching. It also serves as a handy reference for those interested in key CA findings on social interaction"--
OCLC-licensed vendor bibliographic record.
Keywords: Second language acquisition; Language and languages; Language and education; English language -- Study and teaching -- Foreign speakers; EDUCATION / General; EDUCATION / Bilingual Education; EDUCATION / Teaching Methods & Materials / General